Psychological Effects of People Isolated in Hubei Due to COVID-19 Epidemic - Gong, Jiaying; Chen, Guanmao; Qi, Zhangzhang; Zhong, Shuming; Su, Ting; Pan, Youling; Wang, Jurong; Huang, Li; Wang, Ying (Frontiers in Psychiatry, 2021)
The Coronavirus Disease 2019 (COVID-19) epidemic broke out from Wuhan in Hubei province, China, spread nationwide and then gradually developed into other countries in the world. The implementation of unprecedented strict isolation measures has affected many aspects of people’s lives and posed a challenge to psychological health. To explored whether people isolated for 14 days due to having contact with COVID-19 patients had more psychosocial problems. We conducted an online survey from February 29 to March 10, 2020. Depression, anxiety, post-traumatic stress disorder (PTSD) symptoms, and coping style were assessed by the Patient Health Questionnaire-9 (PHQ-9), 7-item Generalized Anxiety Disorder Scale (GAD-7), Impact of Event Scale-Revised (IES-R), and Simplified Coping Style Questionnaire-20-Chinese Version. This study included 1315 isolated respondents in Hubei province (58.5% located in Wuhan). 69.3% respondents isolated at home, 30.7% respondents isolated at centralized quarantined spot. Of all respondents, 66.8% reported depressive symptoms, 49.7% reported anxiety symptoms, 89.0% reported PTSD symptoms. Persons who isolated at home was associated with a lower risk of PTSD, depressive and anxiety symptoms (P < 0.01). People who knew someone to have COVID-19 were associated with severe symptoms of PTSD symptoms (P = 0.001). As for coping style, higher level of passive coping style was associated with severe symptoms of PTSD, depression and anxiety (P < 0.001). Our findings identify that person isolated during the COVID-19 epidemic was associated with high proportion of depression, anxiety, and PTSD symptoms. Public health officials should be aware of and prepared to take necessary measures.